Kesehatan Mental dalam Dunia Kerja : Tantangan dan Tanggung Jawab Negara Menuju Indonesia Emas 2045 - Arlene Eleanor (Institut Kewarganegaraan Indonesia, 2024)
Mental health has emerged as a strategic issue in global employment, particularly amid rising work demands and post-pandemic social transformation. In Indonesia, the existing labor regulatory framework does not explicitly address psychosocial risks in the workplace, despite growing psychological burdens among young workers, especially Generation Z. This article examines the integration of mental health into national labor policy through a multidisciplinary lens. It analyzes historical developments, theoretical frameworks such as the Job Demands- Resources Model and Psychosocial Safety Climate, and policy practices from countries including Japan, the United Kingdom, Canada, and Australia. Based on empirical and comparative insights, the article proposes four strategic pillars: regulatory harmonization, social security reform, primary care capacity-building, and multi-stakeholder collaboration with public literacy initiatives. The conclusion emphasizes the critical need to embed mental health in employment systems as a strategic prerequisite to realizing Indonesia’s Vision 2045 and enhancing the competitiveness of its workforce.